2022
DOI: 10.3389/fgene.2022.920273
|View full text |Cite
|
Sign up to set email alerts
|

p53: A Regulator of Ferroptosis Induced by Galectin-1 Derived Peptide 3 in MH7A Cells

Abstract: Backgrounds: Rheumatoid arthritis synovial fibroblasts (RASFs) are the primary cells responsible for destruction of marginal cartilage in rheumatoid arthritis (RA). G1dP3, a bioactive peptide derived from galectin-1 domain, possesses potent anti-inflammatory and anti-proliferation properties in RASFs. This study aimed to determine the effects of G1dP3 ferroptosis induction in RASFs and to further clarify the possible mechanisms.Methods: TNF-α was used to establish a RA model in MH7A cells. Cell Counting Kit-8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…Emerging signaling pathways, such as Xc-GSH-GPX4, FSP1-CoQ10-NAD(P)H, and GCH1-BH4, have been confirmed to be crucial for ferroptosis regulation in musculoskeletal diseases. In the cellular model of TNF-α-induced RA, the bioactive peptide G1dP3 was demonstrated to be a potential therapeutic agent against RA; this effect was correlated with the increased p53-mediated ferroptosis in synovial fibroblasts (Hu et al, 2022b). However, the involvement of ferroptosis regulatory molecules, such as p53, in musculoskeletal diseases still requires further elaboration.…”
Section: Discussion and Future Remarksmentioning
confidence: 99%
“…Emerging signaling pathways, such as Xc-GSH-GPX4, FSP1-CoQ10-NAD(P)H, and GCH1-BH4, have been confirmed to be crucial for ferroptosis regulation in musculoskeletal diseases. In the cellular model of TNF-α-induced RA, the bioactive peptide G1dP3 was demonstrated to be a potential therapeutic agent against RA; this effect was correlated with the increased p53-mediated ferroptosis in synovial fibroblasts (Hu et al, 2022b). However, the involvement of ferroptosis regulatory molecules, such as p53, in musculoskeletal diseases still requires further elaboration.…”
Section: Discussion and Future Remarksmentioning
confidence: 99%
“…Additionally, p53 favors ferroptosis by downregulating SLC7A11 expression to increase ROS levels via spermidine/spermine N1-acetyl transferase (SAT1)-arachidonate15-lipoxygenase (ALOX15). Recent studies suggest that the p53/SLC7A11 signaling axis control ferroptosis in MH7A cells ( Hu et al, 2022 ).…”
Section: Ferroptosis and Rheumatoid Arthritismentioning
confidence: 99%
“…Galectin-1 derived peptide 3 (G1dP3), a bioactive peptide derived from the galectin-1 structural domain, has potent anti-inflammatory effects on RA-FLS ( Hu et al, 2020 ). A recent study suggests G1dP3 promotes ferroptosis in RA-FLS via the p53/SLC7A11 axis and has potential therapeutic effects ( Hu et al, 2022 ).…”
Section: Use Of Ferroptosis-related Drugs In Rheumatoid Arthritis Tre...mentioning
confidence: 99%
“…p53 can inhibit the expression of SLC7A11 at the transcriptional level and subsequently reduce the biosynthesis of GSH, thus inducing ferroptosis and suppressing tumor growth ( Hu et al, 2022 ). In 2019, Gu Wei et al demonstrated that the p53-SLC7A11 axis can also promote ferroptosis in a GSH-independent manner ( Liu and Gu, 2022 ).…”
Section: Mechanisms Underlying Ferroptosismentioning
confidence: 99%